Unexpected Insulating Polymer Maneuvered Solar CO2‐to‐Syngas Conversion - Mo, Qiao‐Ling; Li, Jia‐Le; Xu, Shu‐Ran; Wang, Kun; Ge, Xing‐Zu; Xiao, Yang; Wu, Gao; Xiao, Fang‐Xing (Advanced functional materials, 2023)
CO2 reduction to carbon feedstocks using heterogeneous photocatalysis technique has been deemed as an attractive means of addressing both deteriorating greenhouse effect and depletion of fossil fuels. Nevertheless, deficiency of accessible active sites on the catalyst surface, low CO2 adsorption rate, and short carrier lifetime retard the photocatalytic CO2 conversion into hydrocarbon fuels. In this study, the controllable construction of spatially separated directional charge transport pathways over multilayered heterostructured transition metal chalcogenides (TMCs) based photosystems for high‐performance photocatalytic CO2‐to‐syngas conversion are shown. In this scenario, ultrathin non‐conjugated insulating poly(diallyl‐dimethyl‐ammonium chloride) (PDDA) layer are intercalated in‐between TMCs and layered double hydroxide (LDH) and serve as an efficient electron transfer mediator, whilst LDH functions as a hole‐withdrawing regulator, both of which synergistically foster the spatial vectorial charge migration/separation over TMCs, thus endowing the TMCs/PDDA/LDH heterostructures with significantly boosted visible‐light‐driven photoactivity toward CO2 conversion into syngas. This study can inspire sparkling new ideas to realize fine tuning of charge motion for stimulating solar‐to‐fuel conversion. Ultrathin non‐conjugated insulating poly(diallyl‐dimethyl‐ammonium chloride) (PDDA) serves as an efficient electron transfer mediator, and simultaneously layered double hydroxide (LDH) functions as a hole‐withdrawing regulator, both of which synergistically contributes to the spatially separated bi‐directional charge transfer pathways over transition metal chalcogenides toward significantly boosted CO2 photoreduction catalysis under visible light irradiation.